(untitled) (Eurasian Medical Research Periodical, 2022)
It has been shown that the course of myocardial infarction in women, especially after 40 years, is characterized by the severity of complications, such as heart ruptures, cardiogenic shock, asystole, recurrent ventricular fibrillation and EMD, which provide a large percentage of deaths. The lethality of women in the fifth decade of life is especially high, and at the age of 50 to 59 years, the highest incidence of repeated large-focal necrosis was noted, while small-focal myocardial infarctions, including repeated ones, were detected in patients aged 45 to 55 years. which is more common than in women under 60 years of age.